Tantangan dan Hambatan dalam Menjalankan Peran Khalifah: Studi Kasus Dalam Lingkup Mahasiswa UPN Veteran Jawa Timur - Dewi, Dewi Nuriatul Jannah; A. Muammar Alawi; Sri Defiana Putri; Rizky Amalia Khusna (Indonesian Journal of Islamic Educational Review, 2024)
Islam is a religion that is much sought after by the world's population. Humans as noble and special creatures are an inseparable part of this universe, so Allah SWT has given them various advantages compared to other creatures. The role of humans on earth as caliphs or as leaders on earth is a very strategic role. Challenges and obstacles in carrying out the role of caliph among UPN Veteran East Java students were analyzed using a questionnaire method, data was collected from 50 students to gain in-depth insight into their views on the role and obstacles as caliph in the campus environment. The research results show that the majority of UPN Veteran East Java students have a positive view of the role of the caliph, with 66.3% agreeing or strongly agreeing. As many as 80% of students felt that their friends' views were also very positive, indicating strong social support. However, 58.3% of students admitted that there were challenges and obstacles in carrying out the role of caliph on campus. Strong social support is considered important to overcome the challenges faced in the Industrial Revolution 4.0 era, in line with research which shows that rapid changes in this era require special attention to character education. Keywords: Islamic Religious Education, Khalifah, Questionnaire